Unimail Info-Communicational Software - Andranik E. Mkhitaryan; Aram S. Nanassian; Eduard Z. Matveev (Изд-во НАН РА)
In this paper, the design and features of the independent infocommunicational software resource are presented based on e-mail and SMS technologies, named Unimail. The components of the server and their responsibilities are also considered. Peculiarities of the Unimail’s architecture and principles of workflow are discussed. Acceptable commands and configuration details are described for users.
Keywords: Mathematics; Computer software